PENGARUH ETNOSENTRISME DAN PRODUCT KNOWLEDGE TERHADAP MINAT BELI PRODUK TEMBE MEE DONGGO - Sri Ernawati (Distribusi - Journal of Management and Business, 2019)
The aims of this research are: (1) to know and analyze about etnosentrisme of positive and significance effect of product “Tembe Mee Donggo”. (2) to know and analyze about product knowledge in positive and signicance effect of product “Tembe Mee Donggo”. (3) to know and analyze about etnosentrisme and product knowledge of positive or significance effect of product “Tembee Mee Donggo”. the special aim of this research was to give positive input for weaver of “Tembe Mee Donggo” and for conserved this local product and for government, to give support in morale and material for development of product “Tembee Mee Donggo”. The use of method in this research is using associative method. Location of this research in Bima district, especially in Donggo. The population of this research is all the people in Donggo, who ever used and bought of “Tembe Mee Donggo”. the technique of sampling is using purposive sampling with 50 respondence. The technique of data is analyzed multiple regression linear. The results of the research are: (1) etnosentrisme has positive and significance effect of product “Tembee Mee Donggo”. (2) the product knowledge has positive and significance effect of product “Tembe Mee Donggo”. (3) etnosentrisme and product knowledge has similarity positive and significance effect of product “Tembe Mee Donggo”.